Ti-doped molybdenum-based perovskites as anodes for solid oxide fuel cells - He, Beibei; Wang, Z.; Zhao, Ling; Pan, X.; Wu, X.; Xia, C. (Elsevier SA, 2013)
Ti doping is found to increase the stability of Sr2NiMoO6 perovskite oxides in reducing atmosphere. The composition Sr2TiNi0.5Mo0.5O6 (STNM) is further evaluated as a potential oxide anode for solid oxide fuel cells (SOFCs). Electrical conductivity, thermal expansion coefficient, surface exchange coefficient, chemical diffusion coefficient, and its electrochemical performance in single cells with La0.8Sr0.2-Ga0.8Mg0.2O3-delta (LSGM) electrolytes are investigated. STNM exhibits a high conductivity of 17.5 S cm-1 at 800 °C at anodic atmosphere. The material shows good chemical and thermal expansion compatibilities with LSGM. To investigate the effect of Ti doping on the conduction properties, first-principle calculations are performed using the Vienna Ab initio Simulation. The strong TieO bond is held responsible for the enhanced structural stability of STNM under humidified H2 atmospheres, relative to that of the undoped system. The remarkable cell performance with both H2 and dry CH4 as the fuel indicates the potential ability of STNM to be used as SOFC anodes. These results obtained indicate that Sr2TiNi0.5Mo0.5O6 is a promising material for use as anode for intermediate temperature SOFCs.